2022
DOI: 10.1038/s41374-022-00773-z
|View full text |Cite
|
Sign up to set email alerts
|

The CD146-HIF-1α axis regulates epithelial cell migration and alveolar maturation in a mouse model of bronchopulmonary dysplasia

Abstract: Bronchopulmonary dysplasia (BPD) is the most common challenge in preterm neonates. Retardation of alveolar development characterizes the pulmonary pathology in BPD. In the present study, we explored the roles of the CD146-HIF-1α axis in BPD. We demonstrated that the levels of reactive oxygen species (ROS) and soluble CD146 (sCD1146) were increased in the peripheral blood of preterm neonates with BPD. In alveolar epithelial cells, hyperoxia promoted the expression of HIF-1α and CD146, which reinforced each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
(64 reference statements)
0
3
0
Order By: Relevance
“… 5 , 17 Repairing alveolar epithelial cells is vital for treating lung injury associated with BPD and has been extensively studied to elucidate the molecular mechanisms underlying BPD. 10 , 18 , 19 In our study, we observed that Tat-P readily entered alveolar epithelial cells promoting autophagy and reversing the autophagy inhibition caused by hyperoxia. This suggests that Tat-P induces autophagy in alveolar epithelial cells and promotes cellular repair, which has implications for preventing and treating BPD.…”
Section: Discussionmentioning
confidence: 50%
“… 5 , 17 Repairing alveolar epithelial cells is vital for treating lung injury associated with BPD and has been extensively studied to elucidate the molecular mechanisms underlying BPD. 10 , 18 , 19 In our study, we observed that Tat-P readily entered alveolar epithelial cells promoting autophagy and reversing the autophagy inhibition caused by hyperoxia. This suggests that Tat-P induces autophagy in alveolar epithelial cells and promotes cellular repair, which has implications for preventing and treating BPD.…”
Section: Discussionmentioning
confidence: 50%
“…As previously mentioned, cultured lung alveolar cells only express very little total TN-C [ 40 ]. We previously reported that HIF-1α mediates the migration of alveolar epithelial cells and participates in the progression of BPD [ 41 ]. In the present study, we demonstrated that pulmonary epithelial cells could release more soluble TN-C in response to hyperoxia, a phenomenon that could be connected to the HIF-1α pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although HIF-1α is necessary for lung development, excessive HIF-1α can have counterproductive effects. Animal studies have demonstrated increased HIF-1α levels in BPD models [ 96 ]. Furthermore, mtROS can activate NOX1 in BPD mice [ 97 ].…”
Section: Potential Pathogenesis Of Metabolic Reprogramming In Hyperox...mentioning
confidence: 99%